Form characterization of microhole produced by microelectrical discharge drilling - Ali, Mohammad Yeakub; Hamad, Mohd Hosni; Karim, Ahmad Izwan (Taylor & Francis, 2009)
This article discusses the characterization of form of microholes produced by microelectrical discharge drilling (micro-EDD) on beryllium-copper alloy using tungsten carbide electrode of 300 µm diameter. Using a fixed set of micro-EDD parameters, microholes of different aspect ratio were drilled. The selected form characteristics diameter, roundness, and taper angle were investigated. The hole diameter and roundness were estimated by using scanning electron microscope (SEM) and graphical calculation. The microhole was sectioned to measure the depth and taper angle. The variations of these form characteristics were plotted against aspect ratio. This experimental study showed that diameter, roundness error, and taper angle of the microhole increase with the increase of aspect ratio almost at the same rate. The electrode wear ratio was not insignificant for low aspect ratio microhole. However, it increased sharply with the increase of aspect ratio.